The problem of legitimacy for the post-handover Hong Kong government - Sing, Ming (2001)
The much-publicized reversion of Hong Kong's sovereignty to China on July 1, 1997, has been hailed as a success by many. Politically, it has been pointed out that Hong Kong has scarcely changed since the handover. Nevertheless, the alleged successful transition has also witnessed a number of economic, social, and political crises. Drawing on systematically collected longitudinal data of public opinion, this paper tries to answer two important questions: first, has the quasi-bureaucratic-authoritarian political structure of the post-transition government experienced a "legitimation problem," i.e., a rejection of the political structure as a whole. And second, does social discontent directed at incumbent government officials represent strong bottom-up pressure for faster democratization? The longitudinal data suggest that even when public confidence in the HKSAR government dropped to its lowest level in June 1998, there was no evidence to suggest the quasi-bureaucratic authoritarian system had a legitimation problem, nor was there strong public pressure demanding rapid democratization. The demand for changing the political system has seldom been treated as an important personal concern during the transitional period. While social and economic issues have been of great personal concern for most Hong Kong people, very few of them have demanded democratic changes as a way of restoring confidence. Pressure for bottom-up democratization remains low. - Reproduced
Keywords: Hong Kong - Politics and government; Politics and government